EFFECT OF POTASH AND ONION ON THE NUTRITIONAL AND ANTI-NUTRITIONAL COMPOSITION OF COOKED BROWN-EYED COWPEA. - Abdulazeez, R.; Akhadelor, M. O.; Danazumi, I. B.; Aliyu, A.; Bayero, U.; Auta, J. (FUDMA JOURNAL OF SCIENCES, 2023)
An assessment on the effect of potash and onion on the nutritional and anti-nutritional composition of cooked brown-eyed cowpea was conducted using standard analytical methods. Cowpea seeds were cooked with potash, onions and a mixture of potash and onion. The nutritional composition ranged between 4.66% - 6.96% moisture, 19.69% - 21.88% crude protein, 4.77% - 5.75% lipid, 2.79 - 4.07% ash, 1.00 - 2.00% crude fibre, 64.18 - 67.81% carbohydrate, 0.30 - 0.48mg/100g thymine and 0.8 - 1.40mg/100g riboflavin. The phytate, saponin, oxalate, and tannin of anti-nutrients valued between 0.0002 - 0.0006mg/100g, 0.60 - 2.20mg/100g, 0.0062 - 0.093mg/100g and 0.033 - 0.066mg/100g respectively.  This study revealed that onion increased the nutrients and decreased the anti-nutrients as opposed to potash which decreased the nutrients while increasing the anti-nutrients. Hence, the use of onions is recommended as an additive for cooking brown-eyed cowpea
Keywords: Potash, onions, proximate composition, anti- nutrients, Brown-eyed cowpea